ANALISIS DAMPAK GUNCANGAN HARGA MINYAK MENTAH TERHADAP MAKROEKONOMI INDONESIA: APLIKASI VECTOR ERROR CORRECTION MECHANISM - Michael Andre; Nasrudin Nasrudin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Indonesian Crude Oil Price (ICP) often fluctuates by the shock of world oil prices. Because of its important role, the fluctuations or shocks in ICP will affect Indonesia's macro economy. To overcome this problem, this study analyzes the impact of the crude oil price shocks on Indonesia's macro economy which includes economic growth and the money supply (M2) during 2010-2016 using Vector Error Correction Mechanism (VECM). The results show that short-term fluctuations of ICP have a significant and positive effect on economic growth but have a non-significant effect on the money supply. In the long term equilibrium, ICP have a positive and significant effect to both economic growth and money supply which in line with Impulse Response Function (IRF) and Decomposition of Variance (FEDV) analysis. Given its positive impact, the recent decline in oil prices will harm the Indonesian economy. Therefore, the government needs to reduce its dependence on crude oil exports and accurately predict the crude oil price in the future.